Deep Photoacoustic/Luminescence/Magnetic Resonance Multimodal Imaging in Living Subjects Using High‐Efficiency Upconversion Nanocomposites - Liu, Yu; Kang, Ning; Lv, Jing; Zhou, Zijian; Zhao, Qingliang; Ma, Lingceng; Chen, Zhong; Ren, Lei; Nie, Liming (Advanced materials (Weinheim), 2016)
A gadolinium‐doped multi‐shell upconversion nanoparticle under 800 nm excitation is synthesized with a 10‐fold fluorescence‐intensity enhancement over that under 980 nm. The nanoformulations exhibit excellent photoacoustic/luminescence/magnetic resonance tri‐modal imaging capabilities, enabling visualization of tumor morphology and microvessel distribution at a new imaging depth.